Swakaryaloka: Naturalist based street chic creation - Anak Agung Sagung Istri Trisnadewi; Tjok Istri Ratna C.S; Anak Agung Gede Rai Remawa (Journal of Aesthetics, Creativity and Art Management, 2022)
The creation of this naturalist-based street chic ready-to-wear fashion was made with the aim of minimizing liquid waste from chemicals and displaying environmentally friendly clothing. The method used is an experimental method with natural dye techniques, namely dyeing or coloring derived from plants and eco print techniques, which are unique in the form of leaf traces with contemporary art. The creative process used is the ten steps of creating a frangipani fashion design, including idea exploration, research, aesthetic element analysis, design development, sample making, promotion, branding affirmations, to the fashion business. The final collection is entitled Swakaryaloka which is a creative work of art in visualizing clothing using natural dyes that utilize the surrounding nature as an object to produce an environmentally friendly fashion product. The creation of this street chic fashion design is adapted to the trend of spirituality, a change in mindset that is more grounded in preserving nature and respect for the work process. There is a total of 9 looks which are divided into three groups, namely memorable, contemporary, and hopeful. The groups displayed environmentally friendly clothing that had a storyline from the condition of the color of the polluted water to the color of the water being clean or normal. Each look is analyzed using design elements and principles using aesthetic theory. Keywords: natural dye, eco print, spirituality, street chic.